Update on Pathogenesis of Sjogren's Syndrome - Sandhya, Pulukool; Theyilamannil Kurien, Biji; Danda, Debashish; Hal Scofield, Robert (Current Rheumatology Reviews, 2017)
Sjogren's syndrome is a common autoimmune disease that presents with sicca symptoms and extraglandular features. Sjogren's syndrome is presumably as common as RA; yet it is poorly understood, underdiagnosed and undertreated. From the usual identity as an autoimmune exocrinopathy to its most recent designate as an autoimmune epithelitis – the journey of SS is complex. We herein review some of the most important milestones that have shed light on different aspects of pathogenesis of this enigmatic disease. This includes role of salivary gland epithelial cells, and their interaction with cells of the innate and adaptive immune system. Non-immune factors acting in concert or in parallel with immune factors may also be important. The risk genes identified so far have only weak association, nevertheless advances in genetics have enhanced understanding of disease mechanisms. Role of epigenetic and environmental role factors is also being explored. SS has also some unique features such as congenital heart block and high incidence of lymphoma; disease mechanisms accounting for these manifestations are also reviewed.
Keywords: Sjogren' s syndrome